Analysis of Students' Mathematical Concept Representation Ability in Solving Space Building Questions - Marwa Astriani Kamsurya (Lembaga Intelektual Muda (LIM) Maluku, 2021)
The purpose of this study is to describe the ability to represent the mathematical concept of students in solving spatial building problems. The type of research used is qualitative descriptive. Data is collected using tests, interviews, and documentation. Tests and interviews are conducted to learn more about the ability to represent the mathematical concept of students in solving the problem of building a room. The subjects in this study were two people, obtained from 30 students through a test of subject networking. The results of the data analysis showed that the ability to representation of mathematical concepts of students arises when presented mathematical problems, namely visual ability, symbolic ability and verbal ability. Visual capabilities in the form of images are to create geometric building images to explain problems and facilitate their resolution; symbolic ability in the form of mathematical equations or expressions by creating mathematical equations or models of the given representation and problem solving by involving mathematical expressions; verbal ability in the form of written words or text that is to write the interpretation of a representation appropriately and write down the steps of solving mathematical problems